Adaptation of a Single-Cone in Prepared Teeth with Two Reciprocating Systems - Florez-Ariza, Jose Elias; Elejalde, David Aristizabal; Cardenas , Yalil Rodrigez; del Castillo , Aron Aliaga; Ruiz Mora , Gustavo Armando; Guillen , Luis Arriola (Iranian Endodontic Journal, 2022)
Introduction: This ex vivo study aimed to compare the adaptation of single gutta-percha cone in teeth prepared with the Wave One Gold and Reciproc Blue reciprocating systems through cone-beam computed tomography. Materials and Methods: A total of 40 recently extracted mono radicular premolars were randomly assigned into two groups (n=20) corresponding to Reciproc Blue and Wave One Gold reciprocating systems and adapted to a single cone system. Each group was evaluated by cone-beam computed tomography at 1 mm, 2 mm and 4 mm from the apical foramen. We evaluated the number of walls adapted by the cone, quality of filling and the number of spaces between the filling and the walls of the root canal. The Mann-Whitney U and T-tests were employed to associate and compare both groups (P<0.05). Results: At 1 mm in the lingual wall the Wave One Gold system did not adapt by 45% compared to 15% with Reciproc Blue (P<0.05). Likewise, the single-cone filling technique of the Reciproc Blue system showed better sealing quality obtaining an ideal category (75%) compared to Wave One Gold (40%) (P<0.05). The amount of space (mm) found between the cone and the filling walls was greater with Wave One Gold. However, these values were not statistically significant. Conclusions: Based on this ex vivo study the better adaptation of root canals and ideal filling condition was more frequent with Reciproc Blue than Wave One Gold system, mainly at 1 mm from the radicular apex.